The Use of Persuassive Approach in Classroom Interaction - Lisanty, Fibri Indira (Universitas Cokroaminoto Palopo, 2016)
In interaction between teachers and students, there are some approaches that the teachers usually apply in teaching process in the classroom but the case here is what kinds of approaches that the students can appropriate. The approach which is not appropriate in the teaching and learning process will have an impact on development of cognitive, affective, and psychomotor students themselves. One of the existing approaches in teaching is persuasive approach, in which this approach can convince the students to adopt the material. This research is qualitative research which uses discourse analysis to analyze the data that the researcher has found. The samples of this research are three classes of sixth grade of Elementary school. The quantities of this class is 25 people for every class and it has been taken in one of course in Makassar, namely JILC. Having done the research, the researcher found that the negative persuasive appeals that to be used in classes and it makes the negative impacts of the studentsâ motivation in teaching and learning process.